1999
DOI: 10.1126/science.285.5426.412
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Graft Versus Host Disease by Inactivation of Host Antigen-Presenting Cells

Abstract: Graft versus host disease, an alloimmune attack on host tissues mounted by donor T cells, is the most important toxicity of allogeneic bone marrow transplantation. The mechanism by which allogeneic T cells are initially stimulated is unknown. In a murine allogeneic bone marrow transplantation model it was found that, despite the presence of numerous donor antigen-presenting cells, only host-derived antigen-presenting cells initiated graft versus host disease. Thus, strategies for preventing graft versus host d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
834
5
13

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,112 publications
(875 citation statements)
references
References 22 publications
21
834
5
13
Order By: Relevance
“…6A). The donor T-cell-host antigen-presenting cell interaction is essential for triggering of the GVH reaction [40]. Therefore, in the induction phase of the GVH reaction, it is likely that gp49B on host DC interacts with donor T cells via integrin a v b 3 or other unidentified ligand(s), and thereby delivers negative signals into the host DC, and then limits the excessive allogeneic T-cell response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6A). The donor T-cell-host antigen-presenting cell interaction is essential for triggering of the GVH reaction [40]. Therefore, in the induction phase of the GVH reaction, it is likely that gp49B on host DC interacts with donor T cells via integrin a v b 3 or other unidentified ligand(s), and thereby delivers negative signals into the host DC, and then limits the excessive allogeneic T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that the recipient's DC trigger a GVH reaction through interaction with allo-reactive donor CD4 1 and CD8 1 T cells [40]. Thus, to examine the possibility of negative regulation by gp49B in the allogeneic reaction in vivo, we employed a lethal GVH disease model, for which sublethally irradiated gp49B À/À or B6 (H-2 b ) recipient mice received BALB/c (H-2 d ) splenocytes intravenously.…”
Section: Treg-mediated Suppression Of Proliferation Was Not Impairedmentioning
confidence: 99%
“…94 42 The resulting CTL response was, in all cases, limited to the haplotype of the immunizing cells, indicating that the efficiency and physiological relevance of cross -priming in vivo are very low or absent. In addition, in an allogeneic bone marrow transplantation model, Shlomchik et al 95 showed that despite the presence of numerous donor APCs, only host -derived APCs presented minor histocompatibility antigens in vivo and initiated graft -versus -host disease. Thus, cross -priming of recipient minor histocompatibility antigens on donor APC was inefficient.…”
Section: Cancer Gene Therapymentioning
confidence: 99%
“…Nearly two decades ago Korngold and Sprent 2 identified mature donor T cells as the fundamental cellular mediators of GVHD in an MHC matched minor antigenic disparate allogeneic BMT. More recently, the critical role of host 3 and donor 4,5 APCs in the development of GVHD has been established. We now know that the fundamental interaction for induction of GVHD, as it is for all adaptive immune responses, is the interaction of donor T cells with APCs and that this interaction is regulated positively or negatively by a plethora of cytokines, chemokines and several immune cell subsets.…”
Section: Introductionmentioning
confidence: 99%